The impact of malignant nipple discharge cytology (NDc) in surgical management of breast cancer patients (2017)
Background The role of nipple discharge cytology (NDc) in the surgical management of breast cancer patients is unclear. We aimed: (i) to evaluate the effect of malignant NDc on the surgical approach to the nipple-areola complex, and (ii) to verify the association between malignant NDc and nipple malignancy. Methods We retrospectively analyzed a case series of 139 patients with NDc who underwent breast surgery. The clinical and histological findings, types of surgery with emphasis on nipple-areola complex amputation, immunohistochemical phenotypes of the carcinomas and measurements of the tumor-nipple distance were recorded. Additionally, in patients who showed HER2-positive lesions on definitive surgery, we evaluated the HER2 immunocytochemistry of the NDc smears. Results Thirty-two malignant and 107 benign/borderline NDc diagnoses were identified. All 32 malignant-NDc cases were histologically confirmed as malignant. Thirty borderline/benign-NDc cases were histologically diagnosed as malignant (sensitivity 58%). The majority of the patients with malignant NDc were treated with nipple-areola complex amputations in both the mastectomy and conservative surgery groups (P<0.001, ?2 51.77). Nipple involvement was strongly associated with HER2-positive ductal carcinoma in-situ (P<0.001, ?2 11.98). HER2 immunocytochemistry on the NDc revealed a 100% correlation with the immunocytochemistry performed on the surgical tissues. Conclusions Malignant NDc influenced surgical management. The association of malignant NDc with nipple involvement is highly related to ductal carcinoma in-situ with HER2 overexpression. In case of HER2 positive NDc, nipple-areola complex involvement is more likely than in HER2 negative cases.